OBESITY AS AN IMMUNOMETABOLIC DISORDER: MECHANISMS OF IMMUNE IMPAIRMENT AND INCREASED SEVERITY OF INFECTIOUS DISEASES - A REVIEW OF CURRENT EVIDENCE - Wiktoria Błaszczyk; Anastasiia Holoborodko; Ewa Wieczorkiewicz; Eliza Garbacz; Agnieszka Pocheć; Bartosz Lautenbach; Dariusz Nędza; Klaudia Wojciech; Anhelina Loputs; Patrycja Stępińska (International Journal of Innovative Technologies in Social Science, 2026)
Background: Obesity represents a major global health burden and is increasingly recognized as a complex immunometabolic disorder rather than a simple imbalance of energy intake and expenditure. Chronic low-grade inflammation, adipokine dysregulation, altered immune cell metabolism, and gut microbiota dysbiosis profoundly remodel immune responses in individuals with obesity. Growing evidence indicates that these alterations significantly affect susceptibility to infections, disease severity, and clinical outcomes, particularly in viral respiratory infections such as COVID-19 and influenza. Aims: This narrative review aims to synthesize current epidemiological, mechanistic, and interventional evidence explaining why individuals with obesity experience more severe courses of infectious diseases. Particular attention is given to immunometabolic dysfunction, adipokine imbalance, inflammasome activation, microbiota-derived immune modulation, and the potential reversibility of immune impairment through metabolic interventions. Methods: A comprehensive narrative literature review was conducted using PubMed, PubMed Central, Google Scholar, and ResearchGate. Eligible studies included randomized controlled trials, observational cohort and cross-sectional studies, mechanistic immunology research, microbiota studies, and systematic or narrative reviews focusing on adults with overweight or obesity. Evidence was synthesized qualitatively due to heterogeneity in study designs and outcomes. Results: Across study types, obesity consistently emerged as an independent risk factor for immune dysfunction and severe infectious outcomes. Mechanistic studies demonstrated chronic activation of inflammatory pathways, including NLRP3 inflammasome signaling, leptin dominance with reduced adiponectin, impaired interferon responses, mitochondrial dysfunction, and exhaustion of T and NK cells. Microbiota studies revealed reduced diversity and depletion of short-chain fatty acid–producing bacteria. Clinical studies confirmed higher rates of hospitalization, intensive care admission, prolonged viral shedding, and mortality among individuals with obesity. Interventional studies showed that modest weight loss (5–10%) can partially restore immune function and reduce inflammatory burden. Conclusion: Obesity profoundly impairs immune competence through interconnected metabolic, inflammatory, and microbiota-driven mechanisms, leading to increased susceptibility to infections and worse clinical outcomes. Although immunometabolic dysfunction is partially reversible, further long-term studies are required to determine its impact on clinical risk reduction.